International Protection of the Rights of Forced Migrants in Judgments of the European Court of Human Rights (Part I) (Summary) - D. V. Ivanov (Московский журнал международного права)
The article highlights the role of the European Court of Human Rights in international protection of the rights of migrants and expands on the practice of the Court regarding various rights and freedoms granted by the European convention on human rights and its Protocols (1950).In the first part of the article a specific attention is drawn to the ECHR practice of considering cases of deportation and extradition, including those concerning the Russian Federation.